Engaging stakeholders to design a comparative effectiveness trial in children with uncontrolled asthma. (January 2016) - Erwin, Kim; Martin, Molly A; Flippin, Tara; Norell, Sarah; Shadlyn, Ariana; Yang, Jie; Falco, Paula; Rivera, Jaime; Ignoffo, Stacy; Kumar, Rajesh; Margellos-Anast, Helen; McDermott, Michael; et al.
Aim: To present the methods and outcomes of stakeholder engagement in the development of interventions for children presenting to the emergency department (ED) for uncontrolled asthma.Methods: We engaged stakeholders (caregivers, physicians, nurses, administrators) from six EDs in a three-phase process to: define design requirements; prototype and refine; and evaluate.Results: Interviews among 28 stakeholders yielded themes regarding in-home asthma management practices and ED discharge experiences. Quantitative and qualitative evaluation showed strong preference for the new discharge tool over current tools.Conclusion: Engaging end-users in contextual inquiry resulted in CAPE (CHICAGO Action Plan after ED discharge), a new stakeholder-balanced discharge tool, which is being tested in a multicenter comparative effectiveness trial.